Pelatihan Pembuatan Keju untuk Memenuhi Kebutuhan Nutrisi Tulang dan Gigi Anak Masa Golden age - Rahmawida Putri; Haerul Juhroni (Universitas Prof. Dr. Hazairin, SH, 2021)
The Training of Making Cheese to Meet the Nutritional Needs of Children's Bones and Teeth during the Golden Age Golden age is a golden period of early childhood in conducting exploration activities in shaping children's character. In fulfilling the nutritional intake of children aged 3-5 years, there are 35% of children in Kukulu village who do not consume milk. This is due to the start of various activities of children in playing, so less consumption of milk. It causes the loss of appetite in consuming milk so that there are problems in the growth of children's bones and teeth. The purpose of program was to increase public knowledge in improving children's nutrition by processing milk into cheese so that the benefits and content of milk are maintained. The method of this community service was lecturing about the benefits of milk and the processing into cheese. Than, continued with training of cheese making in overcoming children who are less willing to consume milk. Evaluation data showe that about 80%-100% of the participants got the good and very good understanding about the material. And, about 80%-100% of them satisfied with satisfied with it.